Orientation and Preparation for the Pre-Retirement Period (MPP) Addressed to the Labor Union of PT. Transjakarta - Basuki Toto Rahmanto; Mariah; Dede Agus Supardi; Atep Supriadi; Aida Fajriyah; Bayu Gusti Pangestu; Claudina Santina Putra Pertiwi; Firman Adopati; Hana Nawal Ramadhanti; Reza Bagus Setiawan; Ghifari Alif Auladi (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
The Pre-Retirement Period (MPP) is a critical phase for individuals approaching the end of their careers, whether in government or private sectors. This study aims to enhance the understanding, knowledge, and preparedness of Transjakarta Labor Union members in facing the MPP. The approach includes educational seminars, observations, needs assessments, problem analysis, and the development of solutions covering psychological, health, financial, and post-retirement activity aspects. The program was implemented over three months (October–December 2023) using a participatory method involving Transjakarta Labor Union members through discussions, education, and practical training. Evaluations revealed improved awareness and readiness among participants for MPP challenges, demonstrated by their enthusiasm and questionnaire results indicating the program's benefits. The outcomes contribute to better individual preparedness for retirement, reduced anxiety, and the formulation of more comprehensive retirement strategies. The program's findings are intended for publication in a community service journal to achieve broader impact. Recommendations for program sustainability include more in-depth training and additional materials on psychology and technical aspects of retirement implementation.